2019
DOI: 10.1021/acs.jmedchem.9b01010
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Benzo[cd]indol-2(1H)-ones and Pyrrolo[4,3,2-de]quinolin-2(1H)-ones as Bromodomain and Extra-Terminal Domain (BET) Inhibitors with Selectivity for the First Bromodomain with Potential High Efficiency against Acute Gouty Arthritis

Abstract: The bromodomain and extra-terminal domain (BET) family of proteins are readers which specifically recognize histone-acetylated lysine residues. Each BET bromodomain protein contains two highly homologous domains: the first bromodomain (BD1) and the second bromodomain (BD2). Pan-BET bromodomain inhibition is a potential therapy for various cancers and immune-inflammatory diseases, but only few reported inhibitors show selectivity within the BET family. Herein, we identified a series of benzo­[cd]­indol-2­(1H)-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 60 publications
(101 reference statements)
0
50
0
Order By: Relevance
“…The pharmacological or genetic inhibition of BRD4 alleviates inflammatory response by inhibiting NLRP3 signaling pathways in varous conditions, such as in TNF-primed rat nucleus pulposus cells, 28 monosodium urate-induced acute gouty arthritis, 74 and middle cerebral artery occlusion-mediated glial activation. 75 Mechanistically, BRD4 inhibition decreases the expression of NLRP3 and CASP1 by limiting the transcriptional activity of RELA.…”
Section: Function Of Bets In Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacological or genetic inhibition of BRD4 alleviates inflammatory response by inhibiting NLRP3 signaling pathways in varous conditions, such as in TNF-primed rat nucleus pulposus cells, 28 monosodium urate-induced acute gouty arthritis, 74 and middle cerebral artery occlusion-mediated glial activation. 75 Mechanistically, BRD4 inhibition decreases the expression of NLRP3 and CASP1 by limiting the transcriptional activity of RELA.…”
Section: Function Of Bets In Innate Immunitymentioning
confidence: 99%
“…As mentioned above, it has been proved that the BRD4-NF-κB signaling pathway has a great contribution to the development of gout arthritis, diabetic intervertebral disc degeneration, osteoarthritis, and rheumatoid arthritis. 51,74,98,[175][176][177] Other diseases. BETs are also involved in other diseases due to their immunomodulatory and proinflammatory properties, such as spontaneous preterm birth, preeclampsia, retinal inflammatory disease, inherited retinal degeneration, age-related macular degeneration, and psoriasis.…”
Section: Kidney Diseasesmentioning
confidence: 99%
“…The pool of BRD4 inhibitors continues to grow, with most identified through fragment or structure-based drug design based on properties of known BRD4 inhibitors. [23][24][25][26][27] Additionally, a recent review 28 identified three novel strategies in targeting BRD4, including bivalent BRD4 inhibitors, proteolytic targeting chimeric molecules and re-purposing of kinase inhibitors. The selectivity of inhibitors is also being targeted.…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factors mapping identified several transcription factors, some of which ( ATF2 , BRD4 , CEBPA, CEBPB, CLOCK , ELK4 , FOS , KLF6 , KLF9 , KMT2A ( MLL1 ), MED1 , NR1H4 ( FXR ), RELA ( p65 ), RUNX1 , RXR , SP1 , SPI1 ( PU.1 ), STAT1 , and VDR ) were reported in the literature to regulate IL-1β ( Figure S17 ). Furthermore, BRD4 was implicated in gouty inflammation in the past [ 43 ]. The involved signaling pathways of these transcription factors in gouty inflammation deserve further studies.…”
Section: Discussionmentioning
confidence: 99%